Análise do traçado eletroencefalograma de pessoas com epilepsia do lobo temporal refratária e sua possível associação com biomarcadores inflamatórios periféricos - Ana Paula Gonçalves (2023)
Introduction: epilepsy is one of the most common chronic neurological diseases. Twenty to thirty percent of patients are resistant to treatment with anti-seizure medication. Patients with refractory epilepsy have an activated basal inflammatory profile. The electroencephalogram is the tool by which neuronal activity is measured dynamically and is fundamental in the investigation of epilepsy. There are no studies correlating these two important variables. Objective: to evaluate possible associations between qualitative and quantitative electrographic parameters and peripheral inflammatory markers in patients with refractory temporal lobe epilepsy. Methods: patients with refractory temporal lobe epilepsy were selected, who underwent videoelectroencephalography and peripheral blood was collected on admission. It was made the quantification of cytokines, chemokines and neurotrophic factors, progranulin, IL-33, ST-2, caspase-1, IL-18, TWEAK, TREM-1, BDNF, NGF, GDNF, NT3, NT4/5, inflammatory proteins IL-6, IL-10, IL-12p70, TNF, IL-1β, and IL-8/CXCL8. The values found were correlated with data from qualitative analysis such as organization of background activity, incidence of epileptiform paroxysms, pattern of ictal onset and post-ictal suppression, quantitative analysis, in addition to semiological characteristics of seizures. Result: 23 patients were selected, 20 of them had seizures during monitoring. We found a negative correlation between disease duration and IL1-β levels. When corrected for sex and age, the absolute frequency of seizure onset showed a negative correlation with NGF levels. There was a positive correlation between caspase-1 and NGF levels and the delta-power index of baseline activity and epileptiform paroxysms. A positive correlation was also found between ST2 and NT3 levels and the delta-power index of the first three seconds of ictal activity. There was a negative correlation between IL-6 levels and the delta-power index of wakeful background activity and between BDNF levels and the delta-power index of the ten seconds of post-ictal suppression. Conclusion: The increase in the proportion of slow rhythms of the background activity during wakefulness is associated with the activation of pro-inflammatory pathways through caspase- 1, the increase in the proportion of slow waves in interictal epileptiform paroxysms is associated with an increase in the peripheral neurotrophic factor NGF , the increase in the proportion of slow waves in the first seconds of ictal activity is associated with an increase in pro-inflammatory activity expressed by an increase in ST2 and an increase in molecules related to neuronal repair, NT3. The increase in slow rhythms on the EEG often reflects some degree of encephalopathy and our study suggests that, in patients with TLE, this increase in slow rhythms is associated with the activation of pro-inflammatory pathways.